Penerapan Model Problem Based Learning Berbasis Kolaboratif - Niken, Niken; Fauziah, Anna; Friansah, Drajat (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the improvement of student learning outcomes after learning using a collaborative-based problem-based leaning model in grade VIII students of SMP Negeri 13 Lubuklinggau on the material of building a flat side room. The research method uses quantitative research with quasi-experimental research design. The sample in the study was grade VIII.3 students consisting of 20 students. The results showed that the average pre-test score (30.85) and post-test average score (78.3) increased learning outcomes with an average score of 47.45. It was concluded that descriptively the mathematics learning outcomes of grade VIII students of SMP Negeri 13 Lubuklinggau after the application of the collaborative-based problem-based learning model increased. Keywords: Collaborative, Learning Outcomes, Problem Based Learning